Variation and Change in Ancient Greek Tense, Aspect and Modality : Language Variation and Change - Bentein, Klaas (Amsterdam Studies in Classical Philology Ser, 2017)
‎Contents -- ‎Preface -- ‎List of Figures -- ‎List of Tables -- ‎List of Abbreviations -- ‎List of Contributors -- ‎Chapter 1. Introduction (Bentein, Janse and Soltic) -- ‎Chapter 2. Subjunctive and Optative in Herodotus' Purpose Clauses as Relative Tense Markers (Lillo) -- ‎Chapter 3. Variation in Expressing Temporal and Aspectual Distinctions in Complement Clauses: A Study of the Greek Non-Literary Papyri of the Roman Period (Kavčič) -- ‎Chapter 4. Syntactic Variation with Verbs of Perception and the 'Oblique Imperfect': Once Again on Aspect, Relative Time Reference and Purported Tense-Backshifting in Ancient Greek (Méndez Dosuna) -- ‎Chapter 5. The Gnomic Aorist in Hesiod (Wakker) -- ‎Chapter 6. The Imperfect Unbound. A Cognitive Linguistic Approach to Greek Aspect (Allan) -- ‎Chapter 7. Aktionsart, Aspect and Category Change in the History of Greek (Moser) -- ‎Chapter 8. ‭Ὤφελ‬(‭λ‬)‭ον‬ in Ancient Greek Counterfactual Desiderative Sentences: From Verb to Modal Particle (Revuelta Puigdollers) -- ‎Chapter 9. Modalized Future and Scheduled Present in Coan Inscriptions (Veksina) -- ‎Chapter 10. 'High' and 'Low' in Medieval Greek (Horrocks) -- ‎Chapter 11. Confusion of Moods in Greek Private Letters of Roman Egypt? (Leiwo) -- ‎Chapter 12. Register Variation and Tense/Aspect/Mood Categories in Ancient Greek: Problems and Perspectives (Willi) -- ‎Index locorum -- ‎Index nominum et rerum.